2019
DOI: 10.1016/j.molcel.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Binding Preferences between Ras and Raf Family Members and the Impact on Oncogenic Ras Signaling

Abstract: Highlights d C-Raf binds all Ras proteins equivalently, but B-Raf exhibits selectivity for K-Ras d Raf N-terminal segments and Ras HVR sequences determine binding preferences d C-Raf is critical for downstream transmission of H-Ras-driven signaling d Events that increase B-Raf/C-Raf dimerization augment the B-Raf/H-Ras interaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 36 publications
2
81
1
Order By: Relevance
“…The Ras R123-E143 salt bridge remains present throughout the simulations, even as R143 of the Raf-CRD moves to interact with Ras E143 ( Fig (42) . Furthermore, the asymmetry and flexibility that we observe in the dimer may facilitate a given Ras isoform to accommodate heterodimers of Raf, important in signal activation (43), as CRaf residues N161, E174, and H175 are isoform specific and correspond to Q257, Q270, and R271 in BRaf (Fig.…”
Section: Raf-crd Links To the Active Site Through Loop 8 Across The Dmentioning
confidence: 99%
“…The Ras R123-E143 salt bridge remains present throughout the simulations, even as R143 of the Raf-CRD moves to interact with Ras E143 ( Fig (42) . Furthermore, the asymmetry and flexibility that we observe in the dimer may facilitate a given Ras isoform to accommodate heterodimers of Raf, important in signal activation (43), as CRaf residues N161, E174, and H175 are isoform specific and correspond to Q257, Q270, and R271 in BRaf (Fig.…”
Section: Raf-crd Links To the Active Site Through Loop 8 Across The Dmentioning
confidence: 99%
“…Given the increased affinity of KRAS Q61H for RAF, and the lack of GTPase activity in KRAS Q61H , which would be expected to allow for stable complex formation, we hypothesized that KRAS Q61H , in particular, may show dependence on the formation of RAF dimers. Prior work showed that the D154Q substitution in KRAS was sufficient to disrupt KRAS-KRAS interactions at the cell membrane that occur via the KRAS a4-a5 interface, but did not alter the baseline biochemical properties of KRAS such as GTPase activity or affinity for RAF (39). The D154Q mutation also abolished the suppressive effects of KRAS WT seen in the genetic background of oncogenic KRAS.…”
Section: Kras Q61h Oligomerization and C-raf Dimerization Are Interdementioning
confidence: 99%
“…Isoform-specific signaling is thought to be mediated by differential intracellular localisation that favors preferential coupling to specific effector pathways (4,22,23), and by distinct biochemical properties imparted by allosteric lobe sequence variations between each isoform (24). Recent in vitro analysis revealed distinct binding preferences for Ras-Raf interactions with BRAF binding being highly selective for KRAS whilst CRAF was critical for HRAS-mediated MAP kinase signaling (25). Mutational-specificity is also important for Ras biology (12,(26)(27)(28)(29), and structural and biochemical features underpinning mutational differences in nucleotide cycling, allosteric regulation and GEF, GAP and effector interactions are now being defined (14,25,28,(30)(31)(32).…”
Section: Oncogenic Rasmentioning
confidence: 99%